Challenges for the construction of teaching practices in a time of pandemic - Andrade, Geórgia Priscila Santiago Bastos (2021)
This article aims to analyze the challenges found in the construction of teaching practices during the COVID-19 pandemic, which forced social isolation with the consequent closure of school institutions, on a global scale, as a measure of containment to the dissemination of lethal virus. Initially, from a bibliographic review, an overview of the global health crisis was presented, followed by a survey of the main obstacles faced by education to implement remote education in Brazil as a matter of urgency. Furthermore, it was specifically about the impact on the teacher, because, although the entire school community was affected by the crisis, he is the one who has had the difficult function of teaching at a distance, even though he is not prepared for it. In this chaotic context, a reflection on the teaching practice with a focus on the teachings of Zabala (1998), Cunha (2010), Tardif (2010) and Freire (1996) was proposed in order to show that the immediacy imposed by the crisis cannot overlap ideologies, practices and conducts built over centuries by teachers themselves in the exercise of their profession. It was concluded that the educators need to reformulate their teaching practices in order to adapt to the new reality, but without giving up the post of knowledge producer, committing themselves to the integral education of the student in a way that does not yield to the interests of the market order that sees education as a simple commodity and the teacher as a simple transmitter of information.